Impact of high pressure on high concentration carbon dioxide capture from natural gas by monoethanolamine/N-methyl-2-pyrrolidone solvent in absorption packed column - Tan, L.S. (Elsevier Ltd, 2015)
Carbon dioxide (CO2) removal is an essential step in natural gas (NG) processing to provide high quality gas stream products and minimize operational difficulties. This study aims to investigate the absorption performance of CO2 at high concentration level of 50 from a mixture of CO2-NG gas stream at pressure condition of up to 5MPa for 20wt monoethanolamine (MEA) aqueous solution and MEA hybrid solution consisting of 20wt MEA with 40wt N-methyl-2-pyrrolidone (NMP)+40wt water in a countercurrent packed column. Comparison of absorption performance was also conducted with water and NMP in order to understand the effect of physical absorption by the individual solvent respectively. It was observed that water had minimal physical absorption for CO2. On the contrary, NMP was observed to be an efficient physical absorbent for CO2 on its own. Increased pressure was found to have a positive impact on the CO2 removal performance for water, NMP, MEA aqueous solution and MEA hybrid solution. This trend was especially significant when the pressure was at 5MPa. Â© 2015 Elsevier Ltd.